Tenecteplase in managing acute ischemic stroke: a long-term cost–utility analysis in Iran. (2nd January 2023) - Hajian, Kosar; Abdi Dezfouli, Ramin; Darvishi, Ali; Radmanesh, Ramin; Heshmat, Ramin
ABSTRACT: Background & Aims: The advantage of tenecteplase (TNK) over alteplase (ALT) in managing acute ischemic stroke (AIS) has been reported, but the cost-effectiveness of these two strategies has not received as much attention. The objective of this study was to compare TNK and ALT for the management of AIS patients in Iran in terms of cost-effectiveness. Methods: This study was carried out from the payer's perspective in Iran, with a lifetime horizon. A full economic evaluation model was designed as a decision tree and a Markov model. After defining different Markov states, each health state was assigned a utility value, and quality-adjusted life year (QALY) was estimated using that value. The incremental cost-effectiveness ratio (ICER) was ultimately used for evaluating the comparative cost-effectiveness. Both deterministic and probabilistic sensitivity analyses were carried out. Results: Compared to ALT, TNK can save approximately 4333.81 USD, and is able to increase one unit of QALY while saving approximately 17, 450.29 USD. So, Base-case results showed that TNK strongly dominates ALT. Moreover, the base case results were strongly confirmed by deterministic and probabilistic sensitivity analysis. Conclusions: Base-case and sensitivity analysis showed that TNK is the dominant strategy compared to ALT for the management of AIS patients.